Dethiobacter alkaliphilus gen. nov. sp. nov., and Desulfurivibrio alkaliphilus gen. nov. sp. nov.: two novel representatives of reductive sulfur cycle from soda lakes - Sorokin, D. Yu; Tourova, T. P; Mußmann, Marc; Muyzer, G (Extremophiles : life under extreme conditions, 2008)
Anaerobic enrichments with H₂ as electron donor and thiosulfate/polysulfide as electron acceptor at pH 10 and 0.6 M total Na⁺ yielded two non sulfate-reducing representatives of reductive sulfur cycle from soda lake sediments. Strain AHT 1 was isolated with thiosulfate as the electron acceptor from north-eastern Mongolian soda lakes and strain AHT 2--with polysulfide as the electron acceptor from Wadi al Natrun lakes in Egypt. Both isolates represented new phylogenetic lineages: AHT 1--within Clostridiales and AHT 2--within the Deltaproteobacteria. Both bacteria are obligate anaerobes with respiratory metabolism. Both grew chemolithoautotrophically with H₂ as the electron donor and can use thiosulfate, elemental sulfur and polysulfide as the electron acceptors. AHT 2 also used nitrate as acceptor, reducing it to ammonia. During thiosulfate reduction, AHT 1 excreted sulfite. dsrAB gene was not found in either strain. Both strains were moderate salt-tolerant (grow up to 2 M total Na⁺) true alkaliphiles (grow between pH 8.5 and 10.3). On the basis of the phenotypic and phylogenetic data, strains AHT 1 and AHT 2 are proposed as new genera and species Dethiobacter alkaliphilus and Desulfurivibrio alkaliphilus, respectively.